On the Relation Between the Credit Spread Puzzle and the Equity Premium Puzzle - Chen, Long; Collin-Dufresne, Pierre; Goldstein, Robert S. (Review of Financial Studies, 2009)
Structural models of default calibrated to historical default rates, recovery rates, and Sharpe ratios typically generate Baa-Aaa credit spreads that are significantly below historical values. However, this "credit spread puzzle" can be resolved if one accounts for the fact that default rates and Sharpe ratios strongly covary; both are high during recessions and low during booms. As a specific example, we investigate credit spread implications of the Campbell and Cochrane (1999) pricing kernel calibrated to equity returns and aggregate consumption data. Identifying the historical surplus consumption ratio from aggregate consumption data, we find that the implied level and time variation of spreads match historical levels well.